IMPLEMENTASI GOOD GOVERNANCE PADA LEMBAGA SWADAYA MASYARAKAT (Studi Kasus Pada Aksi Cepat Tanggap Cabang Semarang) - Sektiono, Dwi; Nugraheni, Rini (Diponegoro Journal of Management, 2017)
This research aims to identify, study and understand the organizational management in the non-profit organization Aksi Cepat Tangap Semarang branch with the paradigm of good governance. Using a qualitative case study method with a phenomenon know in depth the various resources required.Aksi  Cepat  Tanggap  committed  to  become a  professional  non-profit  organization  that  makes growing rapidly to gained trust society. The results of this study show that the Aksi Cepat Tanggap had been applied the principles of good governance. Conclusion this study found that when a non- profit  organization to  apply the principles  of  good governance,  non-profit  organizations  may develop rapidly, lasting and gain public confidence.